Metal Ni / V2C MXene fiber heterostructure composite material as well as preparation method and application thereof

By combining metal Ni nanoparticles with V2C MXene nanofibers to form heterostructure composite materials, the problems of insufficient conductivity and poor stability of the catalyst are solved, and the efficiency and stability of the electrocatalytic hydrogen evolution reaction are significantly improved.

CN119800404APending Publication Date: 2025-04-11JIANGXI NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411805700.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, 3d orbital transition metal-based catalysts have problems of insufficient intrinsic conductivity and poor stability in electrocatalytic hydrogen evolution reactions, which limits their performance and service life in long-term operation.

Method used

By combining metal Ni nanoparticles with V2C MXene nanofibers, a heterostructure composite material is formed, and the interaction between the active material and the support is used to optimize the electronic structure of the active center, improve catalytic activity, and enhance the overall structural stability of the material.

Benefits of technology

The kinetic performance and long-term stability of the catalyst during the electrolytic process are significantly improved, and the efficient and long-lasting electrocatalytic hydrogen evolution reaction is achieved, which reduces the reaction energy barrier and accelerates the reaction kinetic process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800404A_ABST
    Figure CN119800404A_ABST
Patent Text Reader

Abstract

The invention relates to a metal Ni / V2C MXene fiber heterostructure composite material as well as a preparation method and application thereof, and belongs to the field of electro-catalysis hydrogen evolution. The composite material comprises metal Ni nanoparticles and V2C MXene nanofibers, a heterostructure is formed between the metal Ni nanoparticles and the V2C MXene nanofibers, and the preparation method comprises the following steps that a reducing agent is added into V2C MXene hydrosol containing nickel salt, Ni < 2 + > is reduced into amorphous Ni-B nanoparticles, V2C MXene is promoted to be curled to form one-dimensional nanofibers, and a precursor is prepared; and in a hydrogen / argon mixed atmosphere, carrying out heat treatment on the precursor in a quartz tube furnace to completely convert the amorphous Ni-B nano-particles into metal Ni nano-particles, thereby obtaining the metal Ni nano-particles. The composite material can be used as an electrolyzed water catalyst. The strategy of coupling and synergistically enhancing the catalytic activity of the metal Ni nanoparticles and the one-dimensional MXene provided by the invention provides a new way for developing a hydrogen production electrocatalyst which is excellent in performance and low in cost and can replace a noble metal material, and has a very wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic hydrogen evolution, and in particular to a metal Ni / V 2 C MXene fiber heterostructure composite material and its preparation method and application. Background Art

[0002] Producing hydrogen by electrolyzing water resources driven by renewable energy can not only realize the green production of hydrogen energy, but also has important significance for reducing dependence on fossil fuels and reducing environmental pollution. However, the hydrogen evolution reaction (HER) in the process of water electrolysis has an extremely high reaction energy barrier, which limits its efficiency and sustainability. Although platinum group precious metal materials are considered to be ideal catalysts due to their excellent HER performance, their high price, resource scarcity and low stability seriously hinder their large-scale commercial application. Therefore, the development of cheap, stable and efficient platinum-based alternative catalysts has become a hot topic of current research. These alternative catalysts can not only reduce costs, but also improve hydrogen production efficiency and the stability of the catalytic process, thereby promoting technological progress and commercial development in fields such as water electrolysis for hydrogen production and fuel cells.

[0003] A large number of studies have found that 3d-orbital transition metal (such as nickel, Ni)-based catalysts are favored due to their high conductivity, high reactivity and low cost, especially when conducting hydrogen evolution reactions in alkaline electrolyte solutions. These characteristics can significantly improve their electrocatalytic efficiency. However, these catalysts also face the problems of insufficient intrinsic conductivity and poor stability, which limits their performance and service life in long-term operation. These problems are mainly manifested in the easy deactivation of the active centers of the catalysts and the easy destruction of the structure in harsh electrochemical environments. Summary of the invention

[0004] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a metal Ni / V 2 CMXene fiber heterogeneous structure composite material and its preparation method and application. In order to solve the problems in the prior art, the applicant has found that by loading the active material on a low-dimensional nanomaterial carrier such as MXene and utilizing the interaction between the active material and the carrier, it is possible to not only optimize the electronic structure of the active center and improve its catalytic activity, but also enhance the overall structural stability of the material. This coupled interface engineering is expected to significantly improve the kinetic performance and long-term stability of the catalyst in the process of water electrolysis, providing new possibilities for achieving efficient and durable electrocatalysis.

[0005] The technical solution of the present invention is as follows:

[0006] The first aspect of the present invention provides a metal Ni / V 2C MXene fiber heterostructure composite material, the composite material comprising metallic Ni nanoparticles and V 2 C MXene nanofibers, the metallic Ni nanoparticles and V 2 C MXene nanofibers form a heterogeneous structure.

[0007] As a preferred embodiment of the present invention, in the composite material, the content of the metal Ni nanoparticles is 15wt% to 35wt%, and the V 2 The content of C MXene nanofibers is 30 wt% to 70 wt%.

[0008] As a preferred embodiment of the present invention, the particle size of the metal Ni nanoparticles is 10nm to 60nm; 2 The diameter of C MXene nanofibers is 10nm~50nm, and the length is 0.5μm~2μm.

[0009] The second aspect of the present invention provides the above-mentioned metal Ni / V 2 The preparation method of C MXene fiber heterostructure composite material comprises the following steps:

[0010] S1. Add the reducing agent to the V containing nickel salt. 2 C MXene aqueous sol, Ni 2+ is reduced to amorphous Ni-B nanoparticles, while promoting V 2 C MXene curls to form one-dimensional nanofibers to produce composite material precursors;

[0011] S2, in a hydrogen / argon mixed atmosphere, heat-treating the composite material precursor in a quartz tube furnace to completely convert the amorphous Ni-B nanoparticles into metallic Ni nanoparticles to obtain metallic Ni / V 2 C MXene fiber heterostructure composites.

[0012] As a preferred embodiment of the present invention, S1 specifically includes the following steps:

[0013] Keep V 2 C MXene aqueous sol was stirred and NiCl was added dropwise 2 6H 2 O ethanol solution, and continue stirring; then, dropwise add the aqueous solution containing the reducing agent, and continue stirring; use deionized water to centrifugally wash the precipitate, and after freeze-drying, obtain a composite material precursor.

[0014] As a preferred embodiment of the present invention, in S1, the reducing agent is NaBH 4 , stirring time is 20 to 40 minutes;

[0015] The V 2 C MXene hydrosol, containing NiCl 2 6H 2 The volume ratio of the ethanol solution of O to the aqueous solution containing the reducing agent is 9-11:4-6:1-3.

[0016] As a preferred embodiment of the present invention, in S1, the V 2 The mass concentration of C MXene hydrosol is 1-2 mg mL -1 ; The NiCl 2 6H 2 The mass concentration of O in ethanol solution is 40-60 mg mL -1 ; The NaBH 4 The mass concentration of the aqueous solution is 30-50 mg·mL -1 .

[0017] As a preferred embodiment of the present invention, S2 specifically includes the following steps:

[0018] Set the temperature control program to perform high-temperature reduction treatment on the composite material precursor, maintain the gas flow rate at 50-70 mL / min and the volume ratio at 5-15% H 2 / 85~95%Ar mixed atmosphere, after the program is completed, it is naturally cooled to room temperature to obtain metal Ni / V 2 C MXene fiber heterostructure composites.

[0019] As a preferred embodiment of the present invention, in S2, the temperature is 4 to 6 °C·min -1 The heating rate is from room temperature to 450-550°C and maintained for 30-90 minutes.

[0020] As a preferred embodiment of the present invention, the preparation method specifically comprises: 2 6H 2 O ethanol solution and NaBH 4 The two solutions were added dropwise to the V 2 C MXene aqueous sol; Stir for 30 min after adding each solution, and then continue the operation; V 2 C MXene hydrosol, containing NiCl 2 6H 2 O ethanol solution and NaBH 4 The volume ratio of the three is 10:5:2; the precursor powder is obtained by centrifugal washing with deionized water and freeze-drying; the gas flow rate is maintained at 60mL / min with 10% H 2 / 90% Ar mixed atmosphere, high temperature reduction treatment of the precursor powder, set the temperature control program, and naturally cool to room temperature after the program is completed to obtain metal Ni / V 2 C MXene fiber heterostructure composites (i.e., Ni NPs@V 2 C NFs).

[0021] The third aspect of the present invention provides the above-mentioned metal Ni / V 2 Application of C MXene fiber heterostructure composites as water electrolysis catalysts.

[0022] The composite material can be used as a water electrolysis catalyst for electrocatalytic hydrogen evolution reaction.

[0023] After testing, the composite material has excellent performance in water electrolysis and hydrogen evolution reaction under alkaline conditions, and a 10 mA cm -2 The current density only requires an overpotential of 96.0 mV, and the Tafel slope is only 46.3 mV·dec -1 .

[0024] The present invention has at least one of the following beneficial effects:

[0025] (1) A novel method based on metal Ni and V was proposed. 2 The interface regulation strategy of C MXene nanofiber synergy achieves highly reproducible and controllable catalyst preparation through a simple and easy-to-operate process;

[0026] (2) Using metal Ni / V 2 The heterogeneous structure design of C MXene nanofibers effectively promotes electron transfer, significantly enhances the catalytic active sites, and increases the number of active sites;

[0027] (3) Prepared Ni NPs@V 2 C NFs materials can reduce the energy barrier of hydrogen evolution reaction and accelerate the reaction kinetics, thus showing excellent hydrogen evolution performance;

[0028] (4) By regulating the interface between 3d orbital transition metals and MXene materials through interface engineering, the present invention significantly optimizes the hydrogen evolution reaction process. This achievement has broad prospects in the design of low-cost, high-stability electrocatalysts and the development of practical electrocatalytic systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The metal Ni / V of Example 1 2 C XRD pattern of MXene fiber heterostructure composites.

[0030] Figure 2 The metal Ni / V of Example 12 C EDX-Mapping image of MXene fiber heterostructure composite material.

[0031] Figure 3 The metal Ni / V of Example 1 2 C SEM image of MXene fiber heterostructure composite.

[0032] Figure 4 The metal Ni / V of Example 1 2 C TEM image of MXene fiber heterostructure composite.

[0033] Figure 5 The metal Ni / V of Example 2 2 Linear voltammetric scan curves of C MXene fiber heterostructure composite as electrocatalyst in 1M KOH.

[0034] Figure 6 The metal Ni / V of Example 2 2 Tafel plot of C MXene fiber heterostructure composite as electrocatalyst.

[0035] Figure 7 The metal Ni / V of Example 2 2 C MXene fiber heterostructure composites as electrocatalysts were tested at a constant 10 mA cm -2 , 20mA·cm -2 、30mA·cm -2 , 40mA·cm -2 , 50mA·cm -2 , 40mA·cm -2 、30mA·cm -2 , 20mA·cm -2 、10mA·cm -2 , 50mA·cm -2 Chronopotentiometry curves for 9000 s at each current density.

[0036] Figure 8 The metal Ni / V of Example 2 2 SEM image of C MXene fiber heterostructure composite after stability test as electrocatalyst. DETAILED DESCRIPTION

[0037] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0038] The surface, interface morphology and structure of the product of the present invention are measured by field emission scanning electron microscopy (SEM) and transmission electron microscopy (TEM); the crystal phase contained in the product is measured by X-ray diffractometer (XRD); the element distribution and composition are measured by energy dispersive X-ray spectrometer imaging (EDX-mapping) equipped with TEM; the electrocatalytic hydrogen evolution reaction performance of the product is measured on Shanghai Chenhua electrochemical workstation.

[0039] Example 1

[0040] The preparation process and steps in this embodiment are as follows:

[0041] (1) Pipette 5 mL of 6 mg mL -1 V 2 C MXene sol (vanadium dicarbide MXene sol) was added to 15 mL of deionized water, and ultrasonicated for 5 min to make the solution uniform, and then kept stirring to obtain V 2 C MXene hydrosol; weigh 0.476gNiCl 2 6H 2 Add O to 10 mL of ethanol, shake to fully dissolve, and add dropwise to the diluted V 2 C MXene hydrosol, and continued stirring for 30 min to obtain a mixed solution;

[0042] (2) Weigh 154.4 mg NaBH 4 The powder was dissolved in 4 ml of deionized water, added dropwise to the above mixture, and stirred for 30 min; the mixture was washed three times by centrifugation with deionized water, and freeze-dried. The obtained sample was the precursor of the composite material;

[0043] (3) Weigh 70 mg of precursor powder into a porcelain boat and place the boat in a tube furnace, maintaining a high-purity 10% H 2 / 90% Ar (v / v) mixed atmosphere (gas flow rate is 60mL / min); set the temperature program for high temperature treatment at 5℃·min -1 The temperature was raised to 500 °C at a rate of 100 °C, kept at that temperature for 60 min, and then cooled naturally to room temperature under the mixed atmosphere. The obtained sample was metal Ni / V 2 CMXene fiber heterostructure composites (i.e., Ni NPs@V 2 C NFs).

[0044] Example 2

[0045] Metal Ni / V 2 Performance test of C MXene fiber heterostructure composite as catalyst for hydrogen evolution reaction in water electrolysis:

[0046] (1) Preparation of electrocatalyst working electrode:

[0047] First, weigh 2.5 mg of the metal Ni / V prepared in Example 1. 2 C MXene fiber heterostructure composite material powder, 20μL 5wt% nafion solution and 480μL ethanol were added to a centrifuge tube; secondly, ultrasonic treatment was performed in an ultrasonic cleaner for more than 30 minutes to form a uniform ink-like catalyst dispersion; finally, 8μL of catalyst ink was evenly dropped on the surface of a 3mm diameter L-shaped glassy carbon electrode using a pipette, and electrochemical testing was performed after it was naturally dried to form a film.

[0048] (2) Electrochemical performance study:

[0049] The electrochemical performance test was carried out on a Shanghai Chenhua electrochemical workstation (model CHI760E). The electrolyte used was 1 mol·L -1 KOH aqueous solution; the three-electrode system used is configured as follows: a glassy carbon electrode modified with an electrocatalyst as the working electrode, a graphite electrode as the auxiliary electrode, and a saturated calomel electrode (SCE) as the reference electrode. According to the Nernst equation, the potential in the test is converted into a reversible hydrogen electrode potential (E RHE );Subtract E from 0V RHE Then it is the HER overpotential η.

[0050] The three-electrode configuration was immersed in the electrolyte and then connected to the workstation. The following operations were performed: (i) -1 The linear voltammetric test is performed at a rate of 1000 to obtain a polarization curve; (ii) based on the data obtained from the polarization curve (potential E RHE and current density j), establish E RHE and log|current density (j, mA cm -2 )| can be used to calculate the Tafel slope of the electrocatalyst during HER; (iii) -2 , 20mA·cm -2 、30mA·cm -2 , 40mA·cm -2 , 50mA·cm -2 , 40mA·cm -2 、30mA·cm -2 , 20mA·cm -2 、10mA·cm -2 , 50mA·cm -2 The chronopotentiometry test was performed at a constant current density for 9000 s to obtain the stability test results of the prepared electrocatalyst working electrode.

[0051] The test results are shown below.

[0052] The metal Ni / V prepared in Example 1 was determined to be 2 In C MXene fiber heterostructure composite materials, the particle size of metal Ni nanoparticles is 10nm~60nm; V 2 The diameter of C MXene nanofibers is 10nm~50nm, and the length is 0.5μm~2μm.

[0053] Figure 1 The metal Ni / V of Example 1 2 XRD pattern of C MXene fiber heterostructure composite. By comparing with the standard card, it can be confirmed that the composite material contains face-centered cubic metal Ni crystals. In addition, due to the growth of metal nickel nanoparticles and V 2 The curling of C itself inhibits the stacking of MXene, resulting in the failure to observe the (002) plane of MXene.

[0054] Figure 2 The metal Ni / V of Example 1 2 EDX-Mapping of C MXene fiber heterostructure composite material. The analysis revealed that the Ni element is mainly attached to the MXene nanofibers in the form of particles, while the V and C elements are evenly distributed on the MXene nanofibers.

[0055] Figure 3 The metal Ni / V of Example 1 2 C SEM image of MXene fiber heterostructure composite material. The material presents a composite structure of Ni metal particles and MXene one-dimensional nanofibers.

[0056] Figure 4 The metal Ni / V of Example 1 2 TEM image of C MXene fiber heterostructure composite material. Figure (a) shows that nano-metal Ni particles grow around the surface of one-dimensional MXene fiber; Figure (b) (high-resolution TEM image) shows that V 2 The interlayer spacing of C MXene (1.05nm) and the 10-fold lattice distance (10d) of 2.00nm were observed, corresponding to the (111) crystal plane of metal Ni. The above structural characterizations all indicate that metal Ni / V 2 Successful preparation of C MXene fiber heterostructure composites.

[0057] Figure 5 The metal Ni / V of Example 2 2 Linear voltammetric scan curve of C MXene fiber heterostructure composite as electrocatalyst in 1MKOH. The test results show that the metal Ni-V 2The C MXene roll heterostructure composite exhibits excellent alkaline HER electrocatalytic activity, which produces 10 mA cm -2 The baseline current density (comparable to that produced by a 12.3% efficient solar device) requires only 96mV overpotential.

[0058] Figure 6 The metal Ni / V of Example 2 2 Tafel curve of C MXene fiber heterostructure composite as electrocatalyst. The figure shows that the Tafel slope of the composite is only 46.3mV·dec -1 The extremely low Tafel slope value indicates that the composite material has fast alkaline hydrogen evolution reaction kinetics.

[0059] Figure 7 The metal Ni / V of Example 2 2 C MXene fiber heterostructure composites as electrocatalysts were tested at a constant 10 mA cm -2 , 20mA·cm -2 、30mA·cm -2 , 40mA·cm -2 , 50mA·cm -2 , 40mA·cm -2 、30mA·cm -2 , 20mA·cm -2 、10mA·cm -2 , 50mA·cm -2 The chronopotential curves of each current density run for 9000s. The test shows that the composite material has outstanding stability, and there is no obvious increase in potential at the same current density after a long reaction time.

[0060] Figure 8 The metal Ni / V of Example 2 2 C SEM image of MXene fiber heterostructure composite material after stability test as electrocatalyst. This image shows that the metal Ni / V 2 The electrode surface is modified with C MXene fiber heterostructure composite material and Nafion. The morphology of the composite material still maintains the same structure as the initial phase after stability testing, which indicates that the composite material has good structural and performance stability as a HER catalyst for water electrolysis.

[0061] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A metal Ni / V2C MXene fiber heterostructure composite material, characterized in that: The composite material includes metal Ni nanoparticles and V2C MXene nanofibers, and a heterogeneous structure is formed between the metal Ni nanoparticles and the V2C MXene nanofibers.

2. The metal Ni / V2C MXene fiber heterostructure composite material according to claim 1, characterized in that: In the composite material, the content of the metal Ni nanoparticles is 15wt% to 35wt%, and the content of the V2C MXene nanofibers is 30wt% to 70wt%.

3. The metal Ni / V2C MXene fiber heterostructure composite material according to claim 1, characterized in that: The particle size of the metal Ni nanoparticles is 10nm to 60nm; the diameter of the V2C MXene nanofibers is 10nm to 50nm, and the length is 0.5μm to 2μm.

4. The method for preparing the metal Ni / V2C MXene fiber heterostructure composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Add a reducing agent to the V2C MXene aqueous sol containing nickel salt to make Ni 2+ It is reduced to amorphous Ni-B nanoparticles, and at the same time, V2C MXene is curled to form one-dimensional nanofibers to obtain a composite material precursor; S2. In a hydrogen / argon mixed atmosphere, the composite material precursor is heat-treated in a quartz tube furnace to completely convert the amorphous Ni-B nanoparticles into metal Ni nanoparticles to obtain a metal Ni / V2C MXene fiber heterostructure composite material.

5. The preparation method according to claim 4, characterized in that: The S1 specifically includes the following steps: Keep stirring the V2C MXene hydrosol, add the ethanol solution containing NiCl2·6H2O dropwise, and continue stirring; then, add the aqueous solution containing the reducing agent dropwise, and continue stirring; use deionized water to centrifugally wash the precipitate, and after freeze-drying, obtain a composite material precursor.

6. The preparation method according to claim 5, characterized in that: In S1, the reducing agent is NaBH4, and the stirring time is 20 to 40 minutes; The volume ratio of the V2C MXene hydrosol, the ethanol solution containing NiCl2·6H2O and the aqueous solution containing the reducing agent is 9-11:4-6:1-3.

7. The preparation method according to claim 5, characterized in that: In S1, the mass concentration of the V2C MXene hydrosol is 1-2 mg·mL -1 The mass concentration of the ethanol solution containing NiCl2·6H2O is 40~60mg·mL -1 The mass concentration of the aqueous solution containing NaBH4 is 30-50 mg·mL -1 .

8. The preparation method according to claim 5, characterized in that: S2 specifically includes the following steps: The temperature control program was set to perform high-temperature reduction treatment on the composite material precursor, maintaining a gas flow rate of 50-70 mL / min and a volume ratio of 5-15% H2 / 85-95% Ar mixed atmosphere. After the program was completed, it was naturally cooled to room temperature to obtain a metal Ni / V2C MXene fiber heterostructure composite material.

9. The preparation method according to claim 5, characterized in that: In S2, 4~6℃·min -1 The heating rate is from room temperature to 450-550°C and maintained for 30-90 minutes.

10. Use of the metal Ni / V2C MXene fiber heterostructure composite material according to any one of claims 1 to 3 as a water electrolysis catalyst.

Citation Information

Patent Citations

  • Modified MXenes powder as well as preparation method and application thereof

    CN109207834A

  • Multilayer tubular manganese-based multi-component composite electrode material as well as preparation method and application thereof

    CN114171730A

  • MXene loaded Ni nanoparticle composite hydrogen evolution electrocatalyst and preparation method and application thereof

    CN114457371A

  • Mxene-loaded Pd-Ag bimetal composite nanoparticle hydrogen evolution electrocatalyst as well as preparation method and application of Mxene-loaded Pd-Ag bimetal composite nanoparticle hydrogen evolution electrocatalyst

    CN116145173A

  • MXene-loaded two-dimensional branched PdNi nanosheet heterojunction material as well as preparation method and application thereof

    CN116516387A